Body composition and dietary intake of elite cross-country skiers members of the Greek national team - Papadopoulou, S. K.; Gouvianaki, A.; Grammatikopoulou, M. G.; Maraki, Z.; Pagkalos, I. G.; Malliaropoulos, N.; Hassapidou, M. N.; Maffulli, N. (Asian Journal of Sports Medicine, 2012)
Purpose: To assess the anthropometric characteristics and dietary intake of the Greek national cross-country skiing team.